CLINICO-PATHOLOGICAL PATTERN, CLASSIFICATION AND STAGING OF URINARY BLADDER CARCINOMAS - A FIVE YEARS EXPERIENCE AT A TERTIARY CARE HOSPITAL IN CENTRAL PUNJAB - Naeem, Amjad; Naseem, Nadia; Anwar, Sadia; Butt, Seema; Nagi, Abdul Hanan (Journal of Ayub Medical College Abbottabad, 2015)
Background: In Pakistan, urinary bladder carcinoma is the 8th commonest malignancy while being the fourth commonest cancer in men. The relative occurrence of a particular histological type of bladder carcinoma depends on the clinical setting. Both grade and stage of these cancers are highly correlated with recurrence, progression and patient survival rates. Methods: This cross-sectional study comprised of 122 patients with newly diagnosed operable primary bladder carcinomas who underwent cystoscopy associated transurethral resection of bladder tumour at the Urology Department of Punjab Employees Social Security Hospital, Lahore. All participants completed a detailed questionnaire and underwent an in-depth interview to obtain data. The surgical specimens were referred to the Pathology department. Gross observations of the tumour recorded. Result: A total of 114 cases, classified according to WHO/ISUP criteria, low-grade papillary lesions, comprising Papillary Urothelial Neoplasm of Low Malignant Potential (PUNLMP) and Papillary Low Grade carcinomas, accounted for 43% of tumours. Male to female ratio being 5.3:1 (74%). Lateral walls were involved in 44%, posterior wall in 25.3%, trigone in 10.7%, bladder neck in 7.2%, dome in 5.8%, ureteric orifice in 4.13%, anterior wall in 2% and left ureter in 0.87% cases. Tumour staging revealed an overall 11.5% of tumours with stage Ta and 31.5% with stage T3-4. About 29% tumours were non invasive. About n=13 of low-grade carcinomas and n=68 of high-grade carcinomas were invasive. For tumours classified by WHO/ISUP criteria, the percentage of women was larger for PUNLMP than for the other categories of urothelial tumours (p-value 0.006); no statistically significant difference was found by age or gender with respect to tumour stage (p-value 0.138 and 0.452). Conclusion: Transitional Cell Carcinoma (TCC) is the commonest among middle aged men. Keywords: Urinary bladder carcinoma, Tumour, transitional cell carcinoma, urinary bladder